Hypermethylated APC in serous carcinoma based on a meta-analysis of ovarian cancer. Issue 1 (December 2016) - Shen, Chunyan; Sheng, Qifang; Zhang, Xiaojie; Fu, Yuling; Zhu, Kemiao
Abstract Background The reduced expression of the Adenomatous polyposis coli (APC ) gene, a tumor suppressor gene, through promoter hypermethylation has been reported to play a key role in the carcinogenesis. However, the correlation betweenAPC promoter hypermethylation and ovarian cancer (OC) remains to be clarified. Methods A comprehensive literature search was carried out in related research databases. The overall odds ratio (OR) and corresponding 95 % confidence interval (CI) were used to evaluate the effects ofAPC promoter hypermethylation on OC and clinicopathological characteristics. Results Ultimately, 12 eligible studies were used in our study, including 806 OC samples, 429 normal controls, 109 benign lesions and 75 LMP samples. The pooled OR showed thatAPC promoter hypermethylation was significantly higher in OC than in normal and benign controls (OR = 6.18 and OR = 3.26, respectively). No significant correlation was observed between OC and low malignant potential (LMP) tumors (P  = 0.436). In the comparison of OC and normal controls, subgroup analysis based on race showed that the overall OR ofAPC promoter hypermethylation was significant and similar in Asians and Caucasians (OR = 8.34 and OR = 5.39, respectively). A subgroup analysis based on sample type found that the pooled OR was significantly higher in blood than in tissue (OR = 18.71 and OR = 5.74, respectively). A significant association was not observed betweenAPC promoter hypermethylation and tumor grade or tumor stage. The pooled OR indicated thatAPC promoter hypermethylation was significantly lower in serous carcinoma than in non-serous carcinoma (OR = 0.56, P  = 0.02). No obvious publication bias was detected by Egger's test (allP  > 0.05). Conclusions APC promoter hypermethylation may be linked to the increased risk of OC. It was associated with histological type, but not with tumor grade or tumor stage. Moreover, hypermethylatedAPC may be a noninvasive biomarker using blood samples. Future studies are required to validate these results.